2012
DOI: 10.1111/j.1365-2567.2011.03545.x
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of complement does not impact initiation of xenobiotic‐induced autoimmune disease

Abstract: Summary Deficiency in Daf1, a complement regulatory protein, has been shown to exacerbate development of various autoimmune diseases and recent studies have suggested that this may be explained by Daf1 acting to limit T‐cell hyper‐responsiveness. It has been suggested that the absence of Daf1 aggravates autoimmune disease in a complement‐dependent manner, but others have shown that activation of T cells in the absence of Daf1 can be complement independent. However, the relationship between Daf1, complement com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Experimental CVF administration was once thought to directly stimulate T cells, but such effects were later attributed to mitogen contamination (Rumjanek et al, 1978; Cauvi et al, 2012). Because our disease models were T cell-dependent, we utilized highly-purified CVF from a commercial source for our studies.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental CVF administration was once thought to directly stimulate T cells, but such effects were later attributed to mitogen contamination (Rumjanek et al, 1978; Cauvi et al, 2012). Because our disease models were T cell-dependent, we utilized highly-purified CVF from a commercial source for our studies.…”
Section: Discussionmentioning
confidence: 99%
“…This response, however, could not be explained by increased T-cell activation but rather was explained by increased levels of IFN- γ , IL-2, IL-4, and IL-10 ( Table 2 ) [ 19 ]. Furthermore, depletion of C3 was found to have no major effects on development of mHgIA suggesting that the role of DAF1 in mHgIA is independent of an intact complement system [ 104 ]. This is supported by results showing that C3 levels are not affected following mercury exposure of mHgIA sensitive or resistant strains (Pollard, unpublished results).…”
Section: Daf In Animal Models Of Systemic Autoimmune Diseasementioning
confidence: 99%
“…Several models of systemic autoimmunity exhibit disease independent of an intact complement system, yet an exacerbated phenotype is observed by DAF1 deletion [ 19 , 21 , 76 , 104 , 105 ]. This suggests that complement-independent effects of DAF1 are the major contributors to tolerance induction via the interaction of DAF (CD55) with its natural ligand, CD97.…”
Section: How Does Daf1 Regulate Immune Tolerance?mentioning
confidence: 99%
“…This phenotype is characterized by hypersecretion of interferon (IFN)-γ and IL-2 as well as down-regulation of the inhibitory cytokine IL-10 during antigen restimulation of lymphocytes in vitro [19] . Furthermore, several studies have shown that the absence of Daf1 exacerbates disease in a variety of autoimmune models, including systemic autoimmune disease in the MLR-Faslpr mouse [20] , [21] , focal and segmental glomerulosclerosis [22] and mercury-induced autoimmunity [23] , by enhancing T-cell and autoimmune responses associated with hypersecretion of IFN-γ, IL-12 and IL-17 [19] , [24] , [25] , [26] .…”
Section: Introductionmentioning
confidence: 99%